A feasibility study on cement with addition of Prosopis Juliflora ash as in concrete. (2021) - Dharmaraj, R.; SivaKumar, B.
Abstract: The Concrete is a construction material plays a major role in the Infra structure of the nations. One of the important ingredients of conventional concrete is cement, fly ash or other cementicious material. The issue of environmental global warming due to global effects and expensive nature of the origin of cement quarries make us to switch on to the alternative sources. Lots of researches has been done to replace the cement, sand, aggregate. Most of the admixtures are available in market in the form of chemical composition. But, In this project we study the effect of Prosopis Juliflora wood Ash (Seemaikaruvelam) and replace the by cement with 10%, 20% and 30%. The fine structure of prosopis juliflora ash fills more voids and provides superior pore structure and thereby improvising its strength at later stages due to reduced permeability. Its micro-filling it means, effect reduces pores and voids in concretes and provides better moisture resistivity and thus durability. M30 grade mix of concrete was used and the specimens were tested at 7, 14 and 28 days. Effective use for waste material and thus cost effective and performs as well as naturally occurring sand. The experimental work mainly concluded after evaluation workability and concentrates with compressive strength and split tensile strength and acid attack test on concrete enhanced when admixtures like Sugar added into the concrete Mix. The mechanical properties of prosopis juliflora ash concrete were carried out to determine the effectiveness concrete hardened test i.e. compressive test, splitting tensile test and flexural test.